Wind turbine technology scaling up and manufacturing options - Sulukan, Egemen (My University, 2004)
Rüzgar türbin teknolojisindeki ilerleme, yıllık rüzgar çiftlik kurulumundaki artış oranlarının gereksinime paralel olarak geliştiğini göstermektedir. Rüzgar enerjisi gelişim olan ülkeler yerel rüzgar türbini üretimi için teknolojik gelişim perspektifi saptamak durumundadırlar. Türkiye, geniş rüzgar enerjisi teknik potansiyeli ile Avrupa Birliği'nde yer almak ve yeni üretim teknoloji kapasitesini arttırmak isteğinde bir ülkedir. Bu durumda şu sorular önem kazanmaktadır: ·Hangi rüzgar türbin teknolojisi karar vericiler tarafından imal ettirilir? ·Daha yüksek kapasiteli rüzgar türbinleri dizayn ve imal edilirken hangi teknoloji daha güvenilirdir? Rüzgar gücü teknolojik gelişimi önemli kaynaklar gerektirdiğinden, imalatçılar yüksek kapasiteli rüzgar türbinleri ve gelişimin gereksinimleriyle teknoloji seçenekleri arasında dengeyi sağlayabilecek stratejik bir plana sahip olmalıdır. Bu çalışmada amaç; yukarıdaki sorulara cevap ararken, yatırımcıları yerli rüzgar türbin imalat faaliyetlerinde teknoloji seçimi ile optimal kararı verebilmeleri için gerekli teknik girdilerle donatmaktır. Wind turbine technology development is a demand driven activity proved by the annual installation growth rate of wind farms. The countries that have Wind Energy Development Programmes are in a position to determine the technology development perspectives for locally manufactured wind turbines. The countries with high wind energy technical potential should develop their capacities in new technology manufacturing. These following questions below are needed to be answered correctly: ·Which technology of wind turbines should be promoted by decision makers and manufactured by the manufacturers? ·Which technology is more reliable when the higher capacity wind turbines are designed and manufactured? Since the wind power technology development requires important resources, the manufacturers should have a strategical plan regarding the technology type to be consistent with requirements of scaling up and the higher capacity wind turbines. The aim is to provide and equip the investors with the necessary technical input to make an optimal decision on the technology type of their local / global wind turbine manufacturing activities.
Keywords: Makine Mühendisliği